What Is Left of the Cinematic Apparatus, or Why We Should Retain (and Return to) It - Elsaesser, Thomas (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
In this essay I shall briefly summarize what it was about the original formulation of the cinematic apparatus that seemed crucial; what were subsequently perceived to be its shortcomings; how in my own media-archaeological approach I have tried to extend as well as to relativize/historicise the model of the apparatus/dispositif; and finally, what avenues I see for invigorating the theoretical challenges apparatus theory still poses, now in the context of viewing situations that either pastiche and inflate the original paradigm or completely bypass or ignore it.